Black widow optimization-based optimal PI-controlled wind turbine emulator - Premkumar K.; Vishnupriya M.; Babu T.S.; Manikandan B.V.; Thamizhselvan T.; Ali A.N.; Islam M.R.; Kouzani A.Z.; Parvez Mahmud M.A. (MDPI AG, 2023)
In this article, the parameters of the proportional-integral (PI) controller of the wind turbine (WT) emulator, i.e., proportional and integral gain of the PI controller, are optimized using a black widow optimization algorithm (BWOA). The proposed system is developed and analyzed using MATLAB/Simulink environment. The performance of the BWOA optimized PI controller is compared with a BAT algorithm, particle swarm optimization, and genetic algorithm optimized PI controller to measure the effectiveness of the proposed control system. The developed system is tested for different operating conditions such as static wind speed settings, static pitch angle conditions, step-change in wind speed settings, and step-change in pitch angle settings. Finally, the proposed system is realized in real-time by hardware experimentations. The results of the experimentation are compared with simulation results as well. The presented simulation and hardware result shows good agreement, which confirms the effectiveness of the proposed method. Thereby, the proposed optimization-based PI-controlled wind emulator can be recommended for emulating the characteristics of any type of WT with a low-cost system. 2020 by the authors. Licensee MDPI, Basel, Switzerland.